Water-Saving Technology in Sandy Soil Conditions - Usmonov Nodirjon Botiraliyevich (Web of Journals Publishing, 2023)
The article describes the possibilities of improving the moisture regime of the soil and reducing water consumption by co-planting crops (joint care) in the conditions of sandy soils of the desert region.
Keywords: Co-planting, soil moisture, irrigation rate, water consumption